Examination of Macular Retina and Choroidal Thickness in High Myopic Amblyopia Using Spectral-Domain Optical Coherence Tomography - Wan, Juan; Zhang, Zhengwei; Tian, Yu (Frontiers in Medicine, 2022)
Purpose The aim of this study was to investigate changes in the retinal and choroidal thickness between high myopic amblyopia (HMA), low myopia (LM), moderate myopia (MM), high myopia (HM), and normal group (NG) using a spectral-domain optical coherence tomography (SD-OCT). Materials and Methods A total of 75 Chinese children (128 eyes; mean age 10.5 years) were recruited. Retinal thickness (RT) and choroidal thickness (CT) were measured at different locations including subfoveal (SF), and at 0.5 mm/1.0 mm/1.5 mm/2.0 mm/2.5 mm/3.0 mm to the fovea in superior, nasal, inferior, and temporal sectors using enhanced depth imaging (EDI) system of SD-OCT. Axial length (AL), best-corrected visual acuity (BCVA), and refraction errors were also collected. Results No significant differences were found in subfoveal retinal thickness (SFRT). Moreover, a significantly thinner subfoveal choroidal thickness (SFCT) was found in HMA compared to NG, LM, and MM, but not compared to HM. RT at 0.5 mm to fovea, HMA was significantly thinner compared to LM and MM in the three sectors (superior, inferior, and temporal). Nevertheless, no significant differences were found compared to NG and HM. CT at 0.5 mm to fovea, HMA was the significantly thinnest in all four sectors compared to NG, LM, and MM. RT at 1.0 mm/1.5 mm/2.0 mm/2.5 mm/3.0 mm to fovea, HMA was thinner compared to NG, LM, and MM. CT at 1.0 mm/1.5 mm/2.0 mm/2.5 mm/3.0 mm to fovea, HMA was thinner compared to NG, LM, and MM. At the superior and inferior sectors, HMA showed to be statistically thinner compared with HM. Moreover, SFCT in the HMA, HM, and NG were negatively correlated with AL. Conclusions Thinner retina and choroidal tissue appear to be related to HMA, and thus can be used as useful parameters for discovering the underlying mechanisms of the disease.